Plants Alkaloids Based Compound as Therapeutic Potential for Neurodegenerative - Patel, Rajnish Kumar; Gangwar, Dushyant; Gupta, Harsh; Sharma, Niloy; Kumar, Roshan (Journal for Research in Applied Sciences and Biotechnology, 2023)
Although while getting a restful night's sleep is essential for your mental and physical health, insomnia is very prevalent. More people are turning to complementary and alternative therapies to treat or prevent sleeplessness. For hundreds of years, herbal treatments like valerian, passionflower, lemon balm, lavender, and California poppy have been utilized successfully. After using these herbal medicines, sleep latency was reduced and subjective and objective measures of sleep quality improved. Their sedative and sleep-inducing effects are caused by interactions with several neurotransmitter systems in the brain, according to molecular research. The plant species can be divided into 76 different genera and 32 different families, with the Asteraceae (24.2%) and Lamiaceae (21.1%) being the most prevalent subgroups. Leaves (29%) and flowers (27%), respectively, are used to make the majority of infusions (70%) and decoctions (25%). Just the most well-known taxa—out of the 106 known—are treated here (A. arvensis L., C. nepeta L., C. monogyna Jacq., H. lupulus L., L. nobilis L., L. angustifolia Mill., M. sylvestris L., M. chamomilla L., M. officinalis L., O. basilicum L., P. rhoeas L., P. somniferum L., R. officinalis L., T. platyphyllus Scop., and V. officinalis L.). Further study is required to confirm the therapeutic potential of these substitutes and define the mechanism of action of bioactive compounds because only seven of the fifteen species chosen have been investigated for pharmacological activity as hypnotic-sedatives.